The Use of L-Menthol in Endoscopic Transpapillary Interventions. Prospective Randomized Dual-Center Study - M. A. Anishchenko; M. A. Nazmeev; S. G. Shapovalyants; S. A. Budzinsky; A. V. Rogov; R. R. Zaynutdinov; A. S. Melnikova; E. D. Fedorov; E. N. Platonova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Aim: to study the effect of L-menthol on duodenal peristalsis, the results of cannulation of the papilla, the effectiveness and safety of endoscopic retrograde transpapillary interventions (ERTI).Materials and methods. A prospective two-center randomized placebo-controlled trial was carried out from January to November 2022 in two centers. The study included 126 patients, 69 (54.8 %) men and 57 (45.2 %) women, mean age — 62.1 ± 1.8 years. The inclusion criteria were age 18–75 years, indications for ERTI, absence of previous endoscopic papillotomy, absence of allergy to menthol, consent to participate in the study. After randomization, the main group (“L”) included 70 patients, the control group — 56. Patients in group “L” were irrigated with 25 mL (160 mg) of L-menthol (Spectavium), patients in the control group — with 25 mL of saline solution. Peristaltic activity was studied before and three minutes after administration of the drug. The intensity of peristalsis was assessed according to a modified Hiki scale: 0 points — complete absence of peristalsis; 1 point — single peristaltic waves; 2 points — intense peristalsis, little amenable to straightening at maximum insufflation; 3 points — pronounced peristalsis.Results. Three minutes post-irrigation, the suppression of peristaltic waves was noted in the experimental group “L”: 0 points — 63 (90 %) patients, 1 point — 6 (8.6 %) patients, compared to the control, with no change in peristalsis (p < 0.05). Successful selective cannulation was achieved in 64 (91.4 %) patients of group “L” and in 41 (73.2 %) — of the control group (p < 0.05). Non-cannulation endoscopic papillotomy had to be used in 6 (8.5 %) cases in group “L” and in 14 (25 %) cases in the control group. In general, successful cannulation was achieved in 100 % of patients in group “L”, and in 94.5 % — in the control group (p < 0.05). The duration of the intervention was significantly reduced in group “L” — 40 ± 2.5 vs. 50.3 ± 3.6 min. Among the complications, only intraoperative bleeding was registered (2 (2.9 %) — group “L”, 5 (8.9 %) — the control group), which was eliminated endoscopically in all cases.Conclusion. The use of L-menthol during ERTI helps to achieve noticeable inhibition of peristalsis, promotes successful cannulation, reduces the intervention time, minimizes the risk of intraoperative complications. Thus, L-menthol has demonstrated its effectiveness and safety, which makes it possible to use it in the arsenal of combating enhanced peristalsis during ERTI.